Population health in primary care - Haggstrom, David A.; Gabbay, Robert A.; Miller, William L.; Howard, Jenna; Crabtree, Benjamin F. (Frontiers in Medicine, 2024)
Population health in the United States continues to lag behind other wealthy nations. Primary care has the promise of enhancing population health; however, the implementation of a population health approach within primary care deserves further consideration. Clinicians and staff from a national sample of 10 innovative primary care practices participated in a working 2 conference to reflect upon population health approaches in primary care. A series of small-and large-group discussions were recorded, transcribed, and coded through an immersion/crystallization approach. Two prominent themes emerged: 1) Transitioning to a population health focus generally develops through stages, with early implementation focusing on risk stratification and later, more advanced stages focusing on community health; 2) Several inherent barriers confront implementation of a population health approach, including tensions with patient-centered care, and limitations of health information technology. A broader conceptualization of population health in terms of community health could more effectively allow partnerships among primary care, large health care systems, public health organizations, patients, and other stakeholders in the community.